Sodium-ion battery high-nickel positive electrode material as well as preparation method and application thereof

By adopting a multi-dimensional collaborative optimization strategy in the high-nickel cathode material of sodium ion batteries, the trade-offs on the capacity and life of the material in high-voltage cycles are solved, and the coordinated improvement of high capacity and excellent cycle stability is achieved.

CN120072910AActive Publication Date: 2025-05-30TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510534941.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-05-30
Estimated Expiration
2045-04-27

AI Technical Summary

Technical Problem

The layered oxide cathode material of sodium ion batteries has problems such as low reversible capacity and insufficient cycle stability, making it difficult to take into account high energy density and long cycle life.

Method used

By adopting multi-dimensional collaborative optimization strategies such as lattice anchoring, slip passivation, ion locking and interface entropy control in sodium ion battery high-nickel positive electrode materials, including the introduction of low-valent cations, doping of high-valent metal ions, optimizing migration barriers and covering inorganic shells, the structure and performance of the material are coordinated.

Benefits of technology

The high capacity characteristics and long cycle life of high nickel positive electrode materials have been achieved, breaking through the capacity-life trade-off bottleneck of traditional high nickel sodium electrical materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120072910A_ABST
    Figure CN120072910A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion battery high-nickel positive electrode material and a preparation method and application thereof, the sodium ion battery high-nickel positive electrode material comprises an inner core and a shell, the inner core comprises NauAvLiwNi1-x-yFexMnyDtO2 + alpha, 0.9 < = u < = 1.0, 1.02 < = u + nv < = 1.05, n is the valence of an element A, 0.1 < = w < = 0.2 x, 0.1 < = x < = 0.2, 0.1 < = y < = 0.4, 0.01 < = t < = 0.05, 0.02 < = alpha < = 0.2, the ion valence of A < = + 2, the ion radius is greater than or equal to 0.065 nm, the ion valence of D is greater than or equal to + 3, and the bond energy of D-O is greater than 400 kJ / mol; the shell comprises an inorganic substance with a thermal expansion coefficient of 4 * 10 <-6 >-10 * 10 <-6 > / DEG According to the invention, through regulation and control of lattice anchoring, slippage passivation, migration inhibition and interface entropy control, collaborative optimization of high capacity and long cycle life is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and relates to a high-nickel cathode material for sodium-ion batteries, a preparation method thereof, and an application thereof. Background Art

[0002] Due to the high abundance of sodium resources and significant cost advantages, sodium-ion batteries have become a supplementary technical route for lithium-ion batteries and show great application prospects in the field of large-scale energy storage. However, their industrialization process faces technical bottlenecks in the cathode material system, that is, the current mainstream layered oxide cathodes have core defects of low reversible capacity (generally lower than 150 mAh / g) and insufficient cycle stability, and it is difficult to balance the requirements of high energy density and long cycle life.

[0003] Moreover, the O3-type sodium-ion layered oxide material is prone to multiple irreversible phase transitions of O3→P3→OP2 during high-voltage charge and discharge. Among them, the P3→OP2 phase transition will cause a significant deterioration of reversibility due to the sudden change of the kinetic energy barrier, which will further lead to lattice shear distortion and ion migration path mismatch. Under the condition of a high cut-off voltage of 4.25 V, the lattice oxygen participates in charge compensation to form a metastable OP2 phase, which has a high sodium vacancy concentration and the interlayer slip angle seriously deviates from the initial value, resulting in an increase in the reconstruction resistance of the layered framework and the capacity decay rate. In addition, the relatively large ionic radius of sodium ions (1.02 Å) is prone to cause lattice stress accumulation during repeated insertion and extraction processes, leading to the progressive destruction of the layered structure framework and the splitting of the bulk electronic transport network. Although the increase in the nickel content in the transition metal layer and the charge and discharge voltage can activate multiple redox couples (Ni 2+ / Ni 4+ 、O 2- / O - ) to increase the specific capacity to exceed 175 mAh / g, the high nickel content will also increase the driving force of the P3→OP2 phase transition.

[0004] Based on the above research, it is necessary to provide a high-nickel cathode material for sodium-ion batteries, which breaks through the capacity-life trade-off bottleneck of traditional high-nickel sodium-ion materials through multi-dimensional synergistic optimization of the bulk and surface. Summary of the Invention

[0005] The purpose of the present invention is to provide a high-nickel cathode material for sodium-ion batteries, a preparation method thereof, and an application thereof. The high-nickel cathode material for sodium-ion batteries realizes the synergistic optimization of the high-capacity characteristics and long cycle life of the high-nickel cathode material through multi-level cooperative regulation strategies such as lattice anchoring to prevent structure collapse, interlayer slip passivation, ion migration barrier optimization, and interfacial entropy engineering to stabilize the electrode / electrolyte interface.

[0006] To achieve the purpose of the present invention, the following technical solutions are adopted:

[0007] In a first aspect, the present invention provides a high-nickel cathode material for a sodium-ion battery, and the high-nickel cathode material for a sodium-ion battery includes a core and a shell on the surface of the core;

[0008] The chemical general formula of the core is Na u A v Li w Ni 1-x-y Fe x Mn y D t O 2+α , where 0.9 ≤ u ≤ 1.0, 1.02 ≤ u + nv ≤ 1.05, n is the valence of element A, 0.1x ≤ w ≤ 0.2x, 0.1 ≤ x ≤ 0.2, 0.1 ≤ y ≤ 0.4, 0.01 ≤ t ≤ 0.05, 0.02 ≤ α ≤ 0.2, the valence of the metal ion corresponding to element A is ≤ +2, and the corresponding metal ion radius ≥ 0.065 nm, the valence of the metal ion corresponding to element D is ≥ +3, and the D-O bond energy > 400 kJ / mol;

[0009] The shell includes an inorganic substance with a coefficient of thermal expansion of 4×10 -6 / °C to 10×10 -6 / °C.

[0010] Since the high-nickel cathode material for a sodium-ion battery can significantly increase the density of redox active sites by increasing the proportion of transition metal nickel, and activate lattice oxygen to participate in charge compensation in the high-voltage range, thereby releasing a higher specific capacity. However, under high-voltage conditions, the material undergoes a multi-stage phase transition process, in which the formation of the OP2 phase is accompanied by a significant contraction of the sodium layer spacing in the c-axis direction, resulting in irreversible structural defects when restoring the O3 phase. At the same time, the dynamic expansion and contraction of the a-b plane lattice induces interlayer shift, and the migration of Fe 3+ and the Jahn-Teller distortion act synergistically, which will cause local stress accumulation and ultimately lead to progressive structural collapse.

[0011] The present invention solves the problems faced by the above high-nickel cathode material through a four-dimensional collaborative regulation strategy, specifically including: (1) Lattice anchoring: Introduce low-valence cations (element A with a metal ion radius ≥ 0.065 nm) into the sodium layer to construct a sodium layer site support network, reduce the volatility of the Na layer spacing, and support a stable sodium layer spacing; (2) Slip passivation: By doping element D with a metal ion valence ≥ +3 and a D-O bond energy > 400 kJ / mol, construct a metal-oxygen bond buffer zone with a high valence and strong bond energy in the transition metal layer to increase the slip resistance of the crystal plane; (3) Ion locking: Incorporate with the dual-site migration characteristics of the sodium / transition metal layer to increase the migration barrier and limit Fe 3+Migration; (4) Interfacial entropy control: Coating a shell with thermodynamic properties matching those of the matrix, that is, coating an inorganic substance with a coefficient of thermal expansion slightly lower than that of the matrix to relieve the structural volume strain and buffer the stress caused by volume changes. Therefore, through multi-dimensional collaborative optimization, the present invention enables the material to achieve a synergistic improvement in high specific capacity and excellent cycle stability during high-voltage cycling, breaking through the capacity-life trade-off bottleneck of traditional high-nickel sodium battery materials.

[0012] The chemical general formula of the core is Na u A v Li w Ni 1-x-y Fe x Mn y D t O 2+α , where 0.9 ≤ u ≤ 1.0, for example, it can be 0.9, 0.92, 0.94, 0.96, 0.98 or 1.0, 1.02 ≤ u + nv ≤ 1.05, for example, it can be 1.02, 1.025, 1.03, 1.035, 1.04, 1.045 or 1.05, n is the valence of element A, 0.1x ≤ w ≤ 0.2x, for example, it can be 0.1x, 0.12x, 0.14x, 0.16x, 0.18x or 0.2x, 0.1 ≤ x ≤ 0.2, for example, it can be 0.1, 0.12, 0.14, 0.16, 0.18 or 0.2, 0.1 ≤ y ≤ 0.4, for example, it can be 0.1, 0.2, 0.3 or 0.4, 0.01 ≤ t ≤ 0.05, for example, it can be 0.01, 0.02, 0.03, 0.04 or 0.05, 0.02 ≤ α ≤ 0.2, for example, it can be 0.02, 0.05, 0.1, 0.15 or 0.2, the valence state of the metal ion corresponding to element A ≤ +2, for example, it can be +2 or +1, and the corresponding metal ion radius ≥ 0.065 nm, for example, it can be 0.065 nm, 0.07 nm, 0.075 nm, 0.08 nm, 0.085 nm or 0.09 nm, the valence state of the metal ion corresponding to element D ≥ +3, for example, it can be +3, +4, +5 or +6, and the D-O bond energy > 400 kJ / mol, for example, it can be 450 kJ / mol, 500 kJ / mol, 550 kJ / mol, 600 kJ / mol or 650 kJ / mol, but not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0013] In the chemical general formula of the core of the present invention, according to the four-dimensional collaborative regulation strategy, the contents of different elements are matched with each other, such as The function is to increase the migration barrier to limit Fe 3+Migration, so 0.1x ≤ w ≤ 0.2x; for another example, element A is doped in the sodium layer to support and stabilize the sodium layer spacing, so 1.02 ≤ u + nv ≤ 1.05.

[0014] The outer shell includes an inorganic substance with a coefficient of thermal expansion of 4×10 -6 / °C to 10×10 -6 / °C, for example, it can be 4×10 -6 / °C, 5×10 -6 / °C, 6×10 -6 / °C, 7×10 -6 / °C, 8×10 -6 / °C, 9×10 -6 / °C or 10×10 -6 / °C, but not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0015] Preferably, the thickness of the outer shell is T (unit: nm), and T is calculated by the following formula: w coating ={[π(r + T) 2 (h + 2T) - πrh 2 ρ shell} / {πrhρ 2 + [π(r + T) core (h + 2T) - πrh 2 ρ 2} × 100%; shell} × 100%;

[0016] Where, w coating is the mass percentage content of the outer shell (unit: %), r is the radius of the inner core (unit: μm), h is the height of the inner core (unit: μm), ρ shell is the density of the outer shell (unit: g / cm 3 ), ρ core is the density of the inner core (unit: g / cm 3 ).

[0017] The values on both sides of the equation of the present invention satisfy the formula for calculating T above.

[0018] The morphology of the inner core of the present invention is quasi-cylindrical, r is the bottom radius of the quasi-cylindrical inner core, and h is the height of the quasi-cylindrical inner core.

[0019] The thickness of the outer shell of the present invention can be calculated by the above formula to effectively solve the problem of characterizing the influence of the coating amount on the material properties. Moreover, this formula creatively calculates the coating thickness of the "cylindrical-like" morphology material, which is completely different from the calculation method of the traditional "spherical" material. This formula is only applicable to the core material type of the present invention because the core of this material can be approximately regarded as a set of cylindrical-like rather than a set of spheres, and this formula is also designed based on the cylindrical core.

[0020] Preferably, the mass percentage content w of the outer shell coating is 0.5% - 2%, for example, it can be 0.5%, 0.7%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0021] The mass percentage content of the outer shell of the present invention in the high-nickel cathode material of the sodium-ion battery is preferably within the above range. On the one hand, adding too little is avoided to prevent the effective function of the outer shell from being affected, and at the same time, adding too much is avoided to prevent the influence on ion transport and cause a sharp increase in the interfacial impedance. On the other hand, when w of the present invention coating is within the above range, a continuous and dense interfacial layer can be formed, significantly reducing the electrolyte corrosion and the excessive growth of the CEI film (cathode electrolyte interface film), effectively alleviating the volume strain during the phase change process, and also reducing the error between the calculated thickness T of the outer shell and the actually measured thickness, improving the accuracy of the calculated thickness T of the outer shell.

[0022] Preferably, the radius r of the core is 2μm - 14μm, for example, it can be 2μm, 4μm, 6μm, 8μm, 10μm, 12μm or 14μm, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0023] Preferably, the height h of the core is 0.1μm - 2μm, for example, it can be 0.1μm, 0.5μm, 1μm, 1.5μm or 2μm, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0024] Preferably, the density ρ of the outer shell shell is 0.5g / cm 3 ~1.8g / cm 3 , for example, it can be 0.5g / cm 3 , 1g / cm 3 , 1.5g / cm 3 or 1.8g / cm 3 , but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0025] Preferably, the density ρ of the corecore is 1.8 g / cm 3 ~2.2 g / cm 3 , for example, it can be 1.8 g / cm 3 , 2.0 g / cm 3 or 2.2 g / cm 3 , but not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0026] Preferably, in the chemical general formula of the core, A includes K + , Ca 2+ , Sr 2+ , Ba 2+ , Cd 2+ , Zn 2+ , Cu 2+ or Mg 2+ or a combination of any one or at least two of them.

[0027] Preferably, in the chemical general formula of the core, D includes Al 3+ , Zr 4+ , Y 3+ , Ti 4+ , Sb 5+ , Cr 6+ , Co 3+ , Ga 3+ , Sc 3 + , Nb 5+ , Ta 5+ , W 6+ , V 5+ , Sn 4+ , Hf 4+ or Mo 6+ or a combination of any one or at least two of them, preferably Sb 5+ , Cr 6+ , Nb 5 + , Ta 5+ , W 6+ , V 5+ or Mo 6+ or a combination of any one or at least two of them.

[0028] Preferably, the valence state of the metal ion corresponding to element D in the present invention is ≥ +5, which can further enhance the lattice rigidity to resist slip deformation.

[0029] Preferably, the outer shell includes ZrSiO 4 , Al 2 SiO 5 , MgSiO 3 , ZrP 2 O 7, Al 2 TiO 5 or MgAl 2 O 4 Any one or a combination of at least two of them, preferably ZrSiO 4 , Al 2 TiO 5 or MgSiO 3 Any one or a combination of at least two of them.

[0030] The outer shell described in the present invention includes inorganic salts and / or composite oxides, and preferably the above compounds, which can not only further enhance the function of the coating layer, but also be more suitable for the calculation formula of the thickness T of the outer shell, and the accuracy of the calculated T is higher.

[0031] In a second aspect, the present invention provides a method for preparing the high-nickel cathode material for a sodium-ion battery as described in the first aspect. The preparation method includes the following steps:

[0032] (1) According to the formula amount, mix and sinter the sodium source, nickel-iron-manganese precursor, A source, D source and lithium source for the first time to obtain a first-sintered material;

[0033] (2) Mix the first-sintered material described in step (1) with the outer shell coating source and sinter it for the second time to obtain the high-nickel cathode material for the sodium-ion battery.

[0034] Preferably, the temperature of the first sintering in step (1) is 900°C to 1250°C, for example, it can be 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, the heat preservation time is 10h to 20h, for example, it can be 10h, 12h, 14h, 16h, 18h or 20h, and the heating rate is 3°C / min to 6°C / min, for example, it can be 3°C / min, 4°C / min, 5°C / min or 6°C / min, but it is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0035] Preferably, the atmosphere of the first sintering in step (1) includes an oxygen-containing atmosphere, such as an air atmosphere or an oxygen atmosphere.

[0036] Preferably, the nickel-iron-manganese precursor in step (1) includes Ni 1-x-y Fe x Mn y (OH) 2 , where 0.1 ≤ x ≤ 0.2, for example, it can be 0.1, 0.12, 0.14, 0.16, 0.18 or 0.2, 0.1 ≤ y ≤ 0.4, for example, it can be 0.1, 0.2, 0.3 or 0.4, but it is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0037] Preferably, the sodium source in step (1) includes any one or a combination of at least two of sodium carbonate, sodium bicarbonate or sodium hydroxide.

[0038] Preferably, the lithium source in step (1) includes any one or a combination of at least two of lithium carbonate, lithium bicarbonate or lithium hydroxide.

[0039] Preferably, after the first sintering in step (1), crushing and sieving are also carried out to obtain the first-sintered material.

[0040] Preferably, the temperature of the second sintering in step (2) is 600 °C to 850 °C, for example, it can be 600 °C, 700 °C, 800 °C or 850 °C, and the heat preservation time is 5 h to 10 h, for example, it can be 5 h, 7 h, 9 h or 10 h, but it is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0041] Preferably, the atmosphere of the second sintering in step (2) includes an oxygen-containing atmosphere.

[0042] Preferably, after the second sintering in step (2), cooling, crushing and sieving are also carried out.

[0043] Preferably, after the second sintering in step (2), the temperature is decreased at a rate of 1 °C / min to 6 °C / min, for example, it can be 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min or 6 °C / min, but it is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0044] In a third aspect, the present invention provides a sodium-ion battery, and the sodium-ion battery includes the high-nickel cathode material for sodium-ion battery as described in the first aspect.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] The present invention solves the problems faced by the above-mentioned high-nickel cathode material through a four-dimensional collaborative regulation strategy, specifically including (1) lattice anchoring: introducing low-valence cations (element A with a metal ion radius ≥ 0.065 nm) into the sodium layer to construct a sodium layer site support network, reducing the volatility of the Na layer spacing, and supporting a stable sodium layer spacing; (2) slip passivation: doping element D with a metal ion valence ≥ +3 and a D-O bond energy > 400 kJ / mol to construct a metal-oxygen bond buffer zone with a high valence and strong bond energy in the transition metal layer, increasing the slip resistance of the crystal plane; (3) ion locking: incorporating , by increasing the migration barrier to limit Fe 3+Migration; (4) Interfacial entropy control: Coating a shell with thermodynamic properties matching those of the matrix, i.e., coating with an inorganic substance having a coefficient of thermal expansion slightly lower than that of the matrix, to alleviate excessive structural volume strain and buffer the stress caused by volume changes. Therefore, through multi-dimensional collaborative optimization, the present invention enables the simultaneous improvement of high specific capacity and excellent cycle stability of the material during high-voltage cycling, breaking through the capacity-life trade-off bottleneck of traditional high-nickel sodium-ion battery materials. Brief Description of the Drawings

[0047] Figure 1 It is a morphology diagram of the high-nickel cathode material for a sodium-ion battery described in Example 1 of the present invention.

[0048] Figure 2 It is a charge-discharge curve diagram of the battery prepared from the high-nickel cathode material for a sodium-ion battery described in Example 1 of the present invention.

[0049] Figure 3 It is a cycle retention rate diagram of the battery prepared from the high-nickel cathode material for a sodium-ion battery described in Example 1 of the present invention. Detailed Description of the Invention

[0050] The technical solution of the present invention will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments are only for helping to understand the present invention and should not be regarded as specific limitations on the present invention.

[0051] Example 1

[0052] This example provides a high-nickel cathode material for a sodium-ion battery. The high-nickel cathode material for a sodium-ion battery includes a core and a shell on the surface of the core; the chemical formula of the core is Na 0.95 Ca 0.04 Li 0.02 Ni 0.6 Fe 0.15 Mn 0.25 Sb 0.0 3 O 2.1 , (wherein, the ionic radius of Ca 2+ is 0.099 nm, and the bond energy of Sb-O is 480 kJ / mol);

[0053] The shell includes ZrSiO 4 (the coefficient of thermal expansion is 4.5×10 -6 / °C); the thickness of the shell is T, and the T is 16 nm, which is calculated by the following formula: w coating = {[π(r + T) 2 (h + 2T) - πr 2 h]ρ shell} / {πr 2 hρ core+[π(r + T) 2 (h + 2T) - πr 2 h]ρ shell}×100%; where, w coating is the mass percentage content of the said outer shell (specifically 1.2%), r is the radius of the said inner core (specifically 8.5 μm), h is the height of the said inner core (specifically 1.08 μm), ρ shell is the density of the said outer shell (specifically 0.72 g / cm 3 ), ρ core is the density of the said inner core (specifically 1.98 g / cm 3 );

[0054] The preparation method of the high-nickel cathode material for sodium-ion batteries in this embodiment includes the following steps:

[0055] (1) According to the formula amount, mix sodium carbonate, nickel-iron-manganese precursor, calcium oxide, antimony oxide and lithium carbonate, and then in an oxygen atmosphere, heat up to 1050 °C at a heating rate of 5 °C / min for the first sintering for 15 h. After pulverization and sieving treatment, a first-sintered material is obtained;

[0056] (2) Mix the first-sintered material obtained in step (1) with ZrSiO 4 , and then in an oxygen atmosphere, perform the second sintering at a temperature of 750 °C for 8 h, and finally cool down to room temperature at a rate of 3 °C / min. After pulverization and sieving treatment, the high-nickel cathode material for sodium-ion batteries is obtained. The morphology diagram of the high-nickel cathode material for sodium-ion batteries is as Figure 1 shown.

[0057] Example 2

[0058] This embodiment provides a high-nickel cathode material for sodium-ion batteries. The high-nickel cathode material for sodium-ion batteries includes an inner core and an outer shell on the surface of the inner core; the chemical formula of the inner core is Na 0.9 Sr 0.06 Li 0.04 Ni 0.65 Fe 0.2 Mn 0.15 Cr 0.0 1 O 2.06 , (where the ionic radius of Sr 2+ is 0.112 nm, and the bond energy of Cr-O is 580 kJ / mol);

[0059] The outer shell includes Al 2 TiO 5 (the thermal expansion coefficient is 9.5×10 -6 / °C); the thickness of the outer shell is T, and the T is 5.2 nm, which is calculated by the following formula: w coating ={[π(r + T) 2 (h + 2T)-πr 2 h]ρ shell} / {πr 2 hρ core +[π(r + T) 2 (h + 2T)-πr 2 h]ρ shell}}×100%; where, w coating is the mass percentage content of the said outer shell (specifically 0.5%), r is the radius of the said inner core (specifically 11.2 μm), h is the height of the said inner core (specifically 1.56 μm), ρ shell is the density of the said outer shell (specifically 1.4 g / cm 3 ) and ρ core is the density of the said inner core (specifically 2.1 g / cm 3 );

[0060] The preparation method of the high-nickel cathode material for sodium-ion batteries in this embodiment includes the following steps:

[0061] (1) According to the formula amount, mix sodium carbonate, nickel-iron-manganese precursor, strontium oxide, chromium oxide and lithium carbonate, and then in an oxygen atmosphere, heat up to 1250 °C at a heating rate of 6 °C / min for the first sintering for 10 h. After pulverization and sieving, the first-sintered material is obtained;

[0062] (2) Mix the first-sintered material described in step (1) with Al 2 TiO 5 , and then in an oxygen atmosphere, perform the second sintering at a temperature of 600 °C for 10 h, and finally cool down to room temperature at a rate of 1 °C / min. After pulverization and sieving, the high-nickel cathode material for sodium-ion batteries is obtained.

[0063] Example 3

[0064] This embodiment provides a high-nickel cathode material for sodium-ion batteries. The high-nickel cathode material for sodium-ion batteries includes an inner core and an outer shell on the surface of the inner core; the chemical formula of the inner core is NaCa 0.025 Li 0.01 Ni 0.7 Fe 0.1 Mn 0.2 Sb 0.0 5 O 2.155 , (where the ionic radius of Ca 2+ is 0.099 nm and the bond energy of Sb-O is 480 kJ / mol);

[0065] The outer shell includes ZrSiO4 (The coefficient of thermal expansion is 4.5×10 -6 / °C); the thickness of the outer shell is T, and the T is 20 nm, which is calculated by the following formula: w coating ={[π(r + T) 2 (h + 2T) - πr 2 h]ρ shell} / {πr 2 hρ core + [π(r + T) 2 (h + 2T) - πr 2 h]ρ shell}×100%; where, w coating is the mass percentage content of the outer shell (specifically 2%), r is the radius of the inner core (specifically 7.2 μm), h is the height of the inner core (specifically 0.82 μm), ρ shell is the density of the outer shell (specifically 0.72 g / cm 3 ), ρ core is the density of the inner core (specifically 1.92 g / cm 3 );

[0066] The preparation method of the high-nickel cathode material for sodium-ion batteries in this embodiment includes the following steps:

[0067] (1) According to the formula amount, mix sodium carbonate, nickel-iron-manganese precursor, calcium oxide, antimony oxide and lithium carbonate, and then in an oxygen atmosphere, heat up to 900 °C at a heating rate of 3 °C / min for the first sintering for 20 h. After pulverizing and sieving, a first-sintered material is obtained;

[0068] (2) Mix the first-sintered material described in step (1) with ZrSiO 4 , and then in an oxygen atmosphere, perform the second sintering at a temperature of 850 °C for 10 h, and finally cool down to room temperature at a rate of 6 °C / min. After pulverizing and sieving, the high-nickel cathode material for sodium-ion batteries is obtained.

[0069] Example 4

[0070] This example provides a high-nickel cathode material for sodium-ion batteries. Except that w coating is 0.1%, so that the thickness T of the outer shell changes adaptively, the rest are the same as in Example 1.

[0071] Example 5

[0072] This example provides a high-nickel cathode material for sodium-ion batteries. Except that w coatingIt is 2.5%, except for the adaptive change in the thickness T of the outer shell, the rest are the same as in Example 1.

[0073] Example 6

[0074] This example provides a high-nickel cathode material for a sodium-ion battery. Except that in the chemical formula of the inner core, Al is used to replace Sb in an equimolar amount, resulting in an adaptive change in the chemical formula of the inner core, the rest are the same as in Example 1.

[0075] Example 7

[0076] This example provides a high-nickel cathode material for a sodium-ion battery. Except that in the chemical formula of the inner core, Zr is used to replace Sb in an equimolar amount, resulting in an adaptive change in the chemical formula of the inner core, the rest are the same as in Example 1.

[0077] Comparative Example 1

[0078] This comparative example provides a high-nickel cathode material for a sodium-ion battery. Except that it does not include an outer shell, the rest are the same as in Example 1;

[0079] The preparation method of the high-nickel cathode material for the sodium-ion battery is the same as that in Example 1 except that ZrSiO is not added during the mixing in step (2) 4 otherwise.

[0080] Comparative Example 2

[0081] This comparative example provides a high-nickel cathode material for a sodium-ion battery. Except that the chemical formula of the inner core is Na 0.95 Ca 0.04 Ni 0.6 Fe 0.15 Mn 0.25 Sb 0.03 O 2.09 otherwise, the rest are the same as in Example 1;

[0082] The preparation method of the high-nickel cathode material for the sodium-ion battery is the same as that in Example 1 except for the adaptive change according to the formula amount.

[0083] Comparative Example 3

[0084] This comparative example provides a high-nickel cathode material for a sodium-ion battery. Except that the chemical formula of the inner core is Na 0.95 Ca 0.04 Li 0.06 Ni 0.6 Fe 0.15 Mn 0.25 Sb0.03 O 2.12 Except for the above, the rest are the same as in Example 1;

[0085] The preparation method of the high-nickel cathode material for sodium-ion batteries is the same as that in Example 1 except for the adaptive change according to the formula amount.

[0086] Comparative Example 4

[0087] This comparative example provides a high-nickel cathode material for sodium-ion batteries. Except that the chemical formula of the core is Na 0.95 Li 0.02 Ni 0.6 Fe 0.15 Mn 0.25 Sb 0.03 O 2.06 Except for the above, the rest are the same as in Example 1;

[0088] The preparation method of the high-nickel cathode material for sodium-ion batteries is the same as that in Example 1 except for the adaptive change according to the formula amount.

[0089] Comparative Example 5

[0090] This comparative example provides a high-nickel cathode material for sodium-ion batteries. Except that the chemical formula of the core is Na 0.95 Ca 0.1 Li 0.02 Ni 0.6 Fe 0.15 Mn 0.25 Sb 0.03 O 2.16 Except for the above, the rest are the same as in Example 1;

[0091] The preparation method of the high-nickel cathode material for sodium-ion batteries is the same as that in Example 1 except for the adaptive change according to the formula amount.

[0092] Comparative Example 6

[0093] This comparative example provides a high-nickel cathode material for sodium-ion batteries. Except that the chemical formula of the core is Na 0.95 Ca 0.04 Li 0.02 Ni 0.6 Fe 0.15 Mn 0.25 O 2.025 Except for the above, the rest are the same as in Example 1;

[0094] The preparation method of the high-nickel cathode material for sodium-ion batteries is the same as that in Example 1 except for the adaptive change according to the formula amount.

[0095] Comparative Example 7

[0096] This comparative example provides a sodium ion battery high nickel positive electrode material, wherein the sodium ion battery high nickel positive electrode material has a core with a chemical formula of Na 0.95 Ca 0.04 Li 0.02 Ni 0.6 Fe 0.15 Mn 0.25 Sb 0.1 O 2.275 Except for this, the rest are the same as in Example 1;

[0097] The preparation method of the sodium ion battery high nickel positive electrode material is the same as that of Example 1 except that the formula amount is adaptively changed.

[0098] The shell thickness T calculated in the above embodiments and comparative examples and the shell thickness T obtained by testing are shown in Table 1, wherein the method for testing the shell thickness T includes observation and measurement under a transmission electron microscope; the sodium ion battery high nickel positive electrode material obtained in the above embodiments and comparative examples and the negative electrode sodium sheet are prepared into a battery, and then the electrochemical performance of the battery is tested, and the test conditions are 2~4.25V, 0.1C discharge in the first week, and then 1C discharge and cycle 50 weeks. The test results are shown in Table 1, wherein the charge and discharge curve of the battery prepared by the sodium ion battery high nickel positive electrode material described in Example 1 is as shown Figure 2 As shown in the figure, the cycle retention rate is as follows Figure 3 As shown by Figure 2 and Figure 3 It can be seen that the battery prepared with the sodium ion battery high nickel positive electrode material described in Example 1 has excellent electrochemical properties.

[0099] Table 1

[0100] From Table 1 we can see that:

[0101] It can be seen from Examples 1-3 and Comparative Example 1 that the present invention uses an inorganic substance with a specific thermal expansion coefficient as a shell for coating, which can buffer the stress caused by volume change, thereby improving the cycle performance of the battery; It can be seen from Examples 1-3 and Comparative Examples 2-3 that the sodium ion battery high nickel positive electrode material of the present invention is also doped with lithium ions to increase the migration barrier to limit Fe 3+ Migration, thereby improving the capacity and cycle performance of the battery, but the amount of lithium ions doped should not be too much. If the lithium ions are doped too much, the residual Li 2O reacts with the electrolyte to form LiF and NaF deposition layers, increasing the interfacial impedance. From Examples 1-3 and Comparative Examples 4-5, it can be seen that in the present invention, a low-valence A element is preferably doped at the sodium site for lattice anchoring to improve the battery performance. However, when too much low-valence A element is doped, it preferentially occupies the sodium layer vacancies, and the reversible deintercalation capacity loss rate of sodium ions increases. From Examples 1-3 and Comparative Examples 6-7, it can be seen that in the present invention, a high-valence D element is preferably doped at the transition metal site for slip passivation to improve the stability of the material and thus the battery performance. However, when too much high-valence D element is doped, the excessive D element occupies the transition metal sites, resulting in lattice contraction and causing excessive local stress concentration. This distortion will hinder the interlayer diffusion of sodium ions. From Example 1 and Examples 4-5, it can be seen that in the present invention, the outer shell preferably has a specific content range to further enhance the matching effect between the outer shell and the inner core and improve the battery performance. From Example 1 and Examples 6-7, it can be seen that in the present invention, the valence state of the doped D element is preferably ≥ +5, so as to further promote the D element to exert the slip passivation effect and further improve the capacity and cycle performance of the battery.

[0102] The above is only the specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A high nickel cathode material for sodium ion batteries, characterized in that: The sodium ion battery high nickel positive electrode material comprises a core and a shell on the surface of the core; The general chemical formula of the core is Na u A v Li w Ni 1-x-y Fe x Mn y D t O 2+α , where 0.9≤u≤1.0, 1.02≤u+nv≤1.05, n is the valence of element A, 0.1x≤w≤0.2x, 0.1≤x≤0.2, 0.1≤y≤0.4, 0.01≤t≤0.05, 0.02≤α≤0.2, the valence state of the metal ion corresponding to element A is ≤+2, and the corresponding metal ion radius is ≥0.065nm, the valence state of the metal ion corresponding to element D is ≥+3, and the D-O bond energy is >400kJ / mol; The housing includes a thermal expansion coefficient of 4×10 -6 / ℃~10×10 -6 / ℃ inorganic matter.

2. The sodium ion battery high nickel positive electrode material according to claim 1, characterized in that The thickness of the shell is T, and T is calculated by the following formula: w coating ={[π(r+T) 2 (h+2T)-πr 2 h]r shell } / {πr 2 h core +[π(r+T) 2 (h+2T)-πr 2 h]r shell }×100%; in, w coating is the mass percentage of the shell, r is the radius of the core, h is the height of the core, ρ shell is the density of the shell, ρ core is the density of the kernel.

3. The sodium ion battery high nickel positive electrode material according to claim 2, characterized in that: The mass percentage of the shell w coating It is 0.5%~2%.

4. The sodium ion battery high nickel positive electrode material according to claim 2 or 3, characterized in that: The radius r of the inner core is 2 μm to 14 μm; And / or, the height h of the inner core is 0.1 μm to 2 μm; and / or, the density of the shell is shell 0.5g / cm 3 ~1.8g / cm 3 ; and / or, the density of the kernel ρ core 1.8g / cm 3 ~2.2g / cm 3 .

5. The sodium ion battery high nickel positive electrode material according to any one of claims 1 to 3, characterized in that: In the general chemical formula of the core, A includes K + , Ca 2+ , Sr 2+ , Ba 2+ 、Cd 2+ 、Zn 2+ , Cu 2+ or Mg 2+ Any one or a combination of at least two of the following: And / or, in the general chemical formula of the core, D includes Al 3+ 、Zr 4+ , Y 3+ 、Ti 4+ , Sb 5+ Cr 6+ 、Co 3+ , Ga 3+ Sc 3+ , Nb 5 + 、 5+ , W 6+ 、V 5+ Sn 4+ , Hf 4+ Or Mo 6+ Any one or a combination of at least two of the following: And / or, the shell includes any one of ZrSiO4, Al2SiO5, MgSiO3, ZrP2O7, Al2TiO5 or MgAl2O4, or a combination of at least two thereof.

6. The sodium ion battery high nickel positive electrode material according to claim 5, characterized in that: In the chemical formula of the core, D includes Sb 5+ Cr 6+ , Nb 5+ 、 5+ , W 6+ 、V 5+ Or Mo 6+ Any one or a combination of at least two of the following: And / or, the shell includes any one of ZrSiO4, Al2TiO5 or MgSiO3 or a combination of at least two thereof.

7. A method for preparing a high-nickel positive electrode material for a sodium ion battery according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) According to the formula, the sodium source, the nickel-iron-manganese precursor, the A source, the D source and the lithium source are mixed and sintered once to obtain a sintered material; (2) The first sintered material in step (1) is mixed with the shell coating source and subjected to secondary sintering to obtain the high-nickel positive electrode material for sodium ion batteries.

8. The preparation method according to claim 7, characterized in that: The primary sintering temperature in step (1) is 900°C to 1250°C, the holding time is 10h to 20h, and the heating rate is 3°C / min to 6°C / min; And / or, the atmosphere of the primary sintering in step (1) includes an oxygen-containing atmosphere.

9. The preparation method according to claim 7 or 8, characterized in that: The secondary sintering temperature in step (2) is 600°C to 850°C, and the holding time is 5h to 10h; and / or, the atmosphere of the secondary sintering in step (2) comprises an oxygen-containing atmosphere; And / or, after the secondary sintering in step (2), the temperature is lowered at a rate of 1°C / min to 6°C / min.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery high-nickel positive electrode material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material and preparation method thereof, positive plate, sodium-ion battery and electric equipment

    CN117080418A

  • Positive electrode material, preparation method thereof and sodium ion battery

    CN117678090A

  • Sodium-ion battery positive electrode material and preparation method thereof, positive electrode plate and sodium-ion battery

    CN117954615A

  • Sodium-ion battery positive electrode material with coating layer, preparation method of sodium-ion battery positive electrode material, sodium-ion battery and application of sodium-ion battery

    CN118448604A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN118676335A